(untitled) (International Congress on Economics, Management and Business Studies, 2026)
In the modern economy, the banking system is one of the main institutional structures that ensure the financial stability of the country. In particular, the effective management of commercial banks’ assets plays an important role in stimulating economic growth, improving the investment climate, and rational use of financial resources.